Current Application of Beta-Tricalcium Phosphate in Bone Repair and Its Mechanism to Regulate Osteogenesis - Lu, Haiping; Zhou, Yinghong; Ma, Yaping; Xiao, Lan; Ji, Wenjun; Zhang, Yi; Wang, Xin (Frontiers in Materials, 2021)
Large segmental bone loss and bone resection due to trauma and/or the presence of tumors and cysts often results in a delay in healing or non-union. Currently, the bone autograft is the most frequently used strategy to manage large bone loss. Nevertheless, autograft harvesting has limitations, namely sourcing of autograft material, the requirement of an invasive procedure, and susceptibility to infection. These disadvantages can result in complications and the development of a bone substitute materials offers a potential alternative to overcome these shortcomings. Among the biomaterials under consideration to date, beta-tricalcium phosphate (β-TCP) has emerged as a promising material for bone regeneration applications due to its osteoconductivity and osteoinductivity properties as well as its superior degradation in vivo. However, current evidence suggests the use β-TCP can in fact delay bone healing and mechanisms for this observation are yet to be comprehensively investigated. In this review, we introduce the broad application of β-TCP in tissue engineering and discuss the different approaches that β-TCP scaffolds are customized, including physical modification (e.g., pore size, porosity and roughness) and the incorporation of metal ions or other materials (e.g., bioactive glass). We subsequently discuss how β-TCP can regulate osteogenic processes to aid bone repair/healing, namely osteogenic differentiation of mesenchymal stem cells, formation of blood vessels, release of angiogenic growth factors, and blood clot formation. By way of this review, a deeper understanding of the basic mechanisms of β-TCP for bone repair will be achieved which will aid in the optimization of strategies to promote bone repair and regeneration.